2021
DOI: 10.1016/j.cegh.2021.100804
|View full text |Cite
|
Sign up to set email alerts
|

Burden of illness of dog-mediated rabies in India: A systematic review

Abstract: India accounts for 35% of global burden of rabies. This systematic review attempts to measure the burden of illness of dog bites and dog-mediated rabies in India. Methods: A systematic literature search was conducted on MEDLINE, EMBASE, Cochrane Central, PROQUEST, Sodhganga and Google Scholar. Two independent reviewers screened titles and abstracts and included full texts as per inclusion criteria. Critical appraisal of included studies was conducted using appropriate checklists. Data was extracted using stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Stray dogs and rabies are a significant problem in India, accounting for 35% of the global disease incidents. 26 Like JMTV, rabies virus was more frequently detected in urban localities ( Figure 6 c; Chi-squared test, p-value = 0·003) although its cumulative normalised abundance was not significantly different between urban and rural environments (Bonferroni adjusted ANOVA test, P = 0·11). Given the increased public awareness of zoonotic diseases and the potential for emergent viruses through human-animal interactions, we included porcine endogenous retrovirus (PERV) E in our analysis ( Figure 6 d).…”
Section: Resultsmentioning
confidence: 92%
“…Stray dogs and rabies are a significant problem in India, accounting for 35% of the global disease incidents. 26 Like JMTV, rabies virus was more frequently detected in urban localities ( Figure 6 c; Chi-squared test, p-value = 0·003) although its cumulative normalised abundance was not significantly different between urban and rural environments (Bonferroni adjusted ANOVA test, P = 0·11). Given the increased public awareness of zoonotic diseases and the potential for emergent viruses through human-animal interactions, we included porcine endogenous retrovirus (PERV) E in our analysis ( Figure 6 d).…”
Section: Resultsmentioning
confidence: 92%
“…Hence, India contributes to approximately one-third of the global rabies burden annually. The disease mainly affects people belonging to a low socio-economic status and children in the age group of 5–15 years in the country [ 4 ]. A systematic review on dog-mediated rabies in India reported that the majority of the dog bites (>60%) in children below 15 years of age are experienced by children in the age group of 7–12 years.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, children (<15 years of age) are more vulnerable (58%) to experiencing 2–4 wounds per encounter. This could be related to their shorter stature and lesser strength to scare away the dogs and may lead to extensive bites, requiring operative interventions and thereby resulting in a greater morbidity and pain associated with bites and their treatment [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, publications on dog bites and related factors are derived from both high-income countries (e.g. Australia, UK, USA) and low-and middleincome countries, as Bangladesh [8], India [9] and Iran [10]. In Poland, to-date, only one attempt has been made to assess the phenomenon [11].…”
Section: Introductionmentioning
confidence: 99%